2023
DOI: 10.3390/en16020853
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of an Inverter Control for Reactive Power Compensation in a Grid-Connected Solar Photovoltaic System Using Sliding Mode Control

Abstract: In photovoltaic (PV) systems, inverters have an essential role in providing an energy supply to meet the demand with power quality. Inverters inject energy into the grid considering that a renewable source is available; however, during intermittent periods or in the absence of power generation, the inverter remains inactive, which decreases the performance of the PV system. One way to increase the operation of inverters is to operate them as Volt-Amps Reactive (VAR) compensators to generate reactive power in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Figure 6 presents an exemplary output current (measured at the secondary side) and flattening of the PV power profile. The reactive power capabilities and control of inverters are still under research; therefore, further progress may be expected [31]. What is important is that the NC RFG specifies requirements regarding energy sources.…”
Section: Grid Codementioning
confidence: 99%
“…Figure 6 presents an exemplary output current (measured at the secondary side) and flattening of the PV power profile. The reactive power capabilities and control of inverters are still under research; therefore, further progress may be expected [31]. What is important is that the NC RFG specifies requirements regarding energy sources.…”
Section: Grid Codementioning
confidence: 99%
“…The aim of FPPT algorithms is to provide grid support at the time of faults in the grid. But FPPT algorithms experience difficulty in maintaining stability in grid at the time of partial shading scenarios [60][61][62][63][64][65].…”
mentioning
confidence: 99%
“…The study demonstrated the effectiveness of their technique across three benchmark IEEE case studies (four-bus, six-bus, and eight-bus systems) compared to other state-of-the-art methods. Flota-Bañuelos et al [10] introduced a control system, consisting of a Sliding Mode Control (SMC) and a Proportional-Integral (PI) voltage control loop, to ensure a disturbance-free energy injection from a photovoltaic (PV) system into the grid. This control system enables the PV inverter to enhance the power factor required by the connected loads, reducing the reactive current demand.…”
mentioning
confidence: 99%